Indigenous People and Social Media Use: Social Media Affordances Actualization of @BaduyCraft and @SaungGunung.id - Rustiraning, Aghnia Kartika (Jurnal Komunikasi, 2022)
Indigenous people in many parts of the world have used social media to fulfill their diverse needs. This process embodies affordances actualization or the realization of potential actions facilitated by communication technology. From digital divide perspective, researchers tend to highlight limited access as the main obstacle in the actualization process. In fact, obstacles can also be influenced by socio-cultural factors such as limited skills and customary prohibitions. Researcher used narrative study approach to explore the experiences and personal reflections of Narman, a young Badui native who runs Instagram accounts @BaduyCraft and @SaungGunung.id, in actualizing social media affordances amid limitations that are closely related to not only access, but also customary provisions, and skills. Through a thematic analysis of interview transcripts and Instagram observations, this study indicates that: limited access and customary prohibitions are not always considered as obstacles in technology usage by indigenous people. Individuals can deal with the absence of electricity and signal by preparing content asynchronously, as well as using customary provisions as guidelines to determine limitations for their social media use. In other words, socio-cultural factors play a very important role in the actualization of social media affordances, including for members of indigenous people.